Pre-sowing treatment of flax seeds with a growth activator and polymer - Barnashova E.K.; Vertikova E.A.; Derevyagin S.S.; Simagin A.D.; Simagina A.S. (BIO Web of Conferences)
Effective work with seed material contributes to an increase in germination and sustainable development of agricultural plants. In this study, experiments were conducted on the pre-sowing treatment of flax seeds with a formulation containing an activator of growth processes – hydrogen peroxide and a polymer of natural origin – inulin, which helps to reduce mucus secretion during semi-dry treatment. The experimental results obtained confirm the effectiveness of the proposed formulation, which helps to increase the germination of plants and facilitates the procedure for performing mechanized stages during technological operations with seed material.